1991
DOI: 10.1007/bf00040640
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA level rhythmicity in the leaves ofSinapis alba during a lengthening of the photoperiod which induces flowering

Abstract: A previous study has shown that mRNAs exhibit complex patterns of diurnal rhythms in their quantity in the leaves of Sinapis alba during an 8 h light/16 h dark short day (SD). In order to determine whether this situation is rapidly modified in plants subjected to an extended light treatment, we have used in vitro translation and two-dimensional polyacrylamide gel electrophoresis, together with a strict gel comparison procedure giving a P = 0.03 certitude level, to analyse the mRNA complement at different times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Cremer et al (1991) analyzed the photoperiodic induction of flowering in the leaves of the SD plant Sinapis alba by looking for changes in the mRNA patterns throughout one photoperiod, comparing SD and LD conditions. They also demonstrated that a lengthening of the light period was able to produce a rapid change in the quantity of some mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Cremer et al (1991) analyzed the photoperiodic induction of flowering in the leaves of the SD plant Sinapis alba by looking for changes in the mRNA patterns throughout one photoperiod, comparing SD and LD conditions. They also demonstrated that a lengthening of the light period was able to produce a rapid change in the quantity of some mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…These changes have been taken as an indication of underlying rhythmic changes in mRNA levels. Lengthening of the light period that induces flowering led to a transient modification of most of the rhythms observed in short days (Cremer et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative changes in in vitro translation products of leaf mRNAs have been found to accompany the photoperiodic flower induction process in S. alba. Some of these changes exhibit a certain periodicity, indicating that they might be under circadian control (Cremer et al, 1990(Cremer et al, , 1991. The nature of transcripts undergoing such alterations has remained elusive, however.…”
Section: Swiss Federal Institute Of Technology (Eth)mentioning
confidence: 99%
“…It is well established that photoperiodic floral induction is regulated by light interacting with underlying endogenous rhythms (Bünning, 1936;Hamner and Takimoto, 1964;reviewed by Vince-Prue, 1986), yet few investigators have analyzed changes in gene expression in relation to photoperiodic floral induction over a 24-h cycle. A single report describes rhythmic changes in mRNA levels associated with photoperiodic induction of flowering in the LDP Sinapis alba (Cremer et al, 1991).…”
mentioning
confidence: 99%